Reactions of Some Endocrine Glands in Male Infant Rats to Acute Hypoxia at the Second Stage of Sexual Maturation - Jabir Mehbaliyeva, Elnara (Journal of Coastal Life Medicine, 2023)
The experiment demonstrated that at the single 20-minute hypoxia of relatively severe form (85% N2 +15% O2) the hormonal reactions from the suprarenal cortex, thyroid gland and testicles in the male infant rats in the age of 2 months at the middle stage of sexual maturation are ambiguous. The adrenocortical hormone (cortisone) in the blood plasma increases at the very first day of hypoxia, and then the reaction dies out. On the 3rd day of experiment the blood level of thyroid gland hormone (thyroxine) increases slightly, and the total testosterone (hormone of testicles and suprarenal cortex) remains within the reference values, and to the 5th day of experiment it decreases substantially in relation to the standard. For the body of human ad animals, especially in the early periods of postnatal ontogenesis, the events of acute oxygen deficiency (О2) (hypoxia) is a life-threatening factor resulting sometimes in its death. According to the literature, the impact of hypoxia causes in the cells and tissues of body the complex, reversible and irreversible changes both of specific and common nature, and many post-hypoxic changes have either adaptive or pathological orientation (Michels C., 2004). Herewith, the mitochondrial biochemical cycles of oxidative phosphorylation which shall provide the body with the sufficient quantity of free energy (ATP) are violated in the course of early (primary) reactions (Lukyanova, L.D., 2001). And the ATP deficit affects negatively the excitability and activity of brain neurons, muscle and gland cells (Samoylov M.O., 1985). Herewith, also the synthesis of a number of functionally important neuropeptides, mediators and hormones (Mishra O.P., Delhoriya M., 1999; Chen X., 2000), conjugation of systemic nervous and neuroendocrine regulation mechanism as well as the performance of a number of cognitive and behavioral functions are violated (Mehbaliyeva E.J., 2014). The reactions of the vegetative nervous system and especially its central link (hypothalamus) occupy the important place in the development of the secondary (late) post-hypoxic effects. It was demonstrated that the hormonal activity of hypothalamic neurosecretory cells and those endocrine glands the functional activity of which is controlled by the neurotropic hormones changes ambiguously in case of hypoxia (Herman R. E. et al., 1994). However, regardless of great success in the development and assessment of the issues of hypoxia a number of aspects of this research direction are currently under- investigated (Mehbaliyeva E.J., 2013). In this regard, in this work the research was aimed at studying the changes in the secretory activity of such important peripheral endocrine glands as suprarenal cortex, thyroid gland and testicles in the male infant rats experimentally affected by hypoxia which were at the second medium stage of sexual maturation.